A report on introduced Amazon sailfin catfish, Pterygoplichthys pardalis in Gombak Basin, Selangor, with notes on two body patterns of the species - Saba, Abdulwakil Olawale; Rasli, Nor Fariza; Ismail, Ahmad; Zulkifli, Syaizwan Zahmir; A. Ghani, Intan Faraha; Muhammad Rasul, Abdullah Halim; Amal, Mohammad Noor Azmai (Universiti Putra Malaysia Press, 2020)
Invasive introduced fish species are well known for their deleterious impacts on aquatic biodiversity and environment. This study provides the first report on the occurrence of introduced Amazon sailfin catfish, Pterygoplichthys pardalis from the Gombak basin, Selangor, Malaysia, where the suckermouth catfish, Hypostomus plecostomus and vermiculated sailfin catfish, Pterygoplichthys disjunctivus had been previously reported. Besides, selected morphometric and meristic measurements between P. pardalis and P. disjunctivus from the Pusu River, Gombak basin were compared. Moreover, we also described two body patterns of the P. pardalis collected from the river. The body pattern which does not fit entirely with the known characteristics of P. pardalis or P. disjunctivus is suspected to be a result of hybridization between both species, but deeper study should be conducted to confirm this claim.